2018
DOI: 10.18203/2349-3291.ijcp20185192
|View full text |Cite
|
Sign up to set email alerts
|

A case series of cyclic vomiting syndrome in paediatric patients at a tertiary care hospital in Chennai, Tamil Nadu, India

Abstract: Background: Cyclic vomiting syndrome is an increasingly recognized disorder with sudden, repeated episodes of severe nausea, vomiting, and physical exhaustion that occur with no apparent cause. It is more common in children than adults. However, we don’t often see a diagnosis of cyclic vomiting syndrome being made. Hereby we report 7 cases of cyclical vomiting.Methods: This is a retrospective study. Medical records of 5 years were review and consecutive paediatric patients discharged with a diagnosis of cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“… 1 Usually, it is characterized by recurrent severe vomiting separated by a long asymptomatic period. 2 It is commonly found in children even though, nowadays cases have also been reported in young adults. 1 , 2 The incidence of CVS was reported 3.15 per 1,00,000 in a study of 1,647 participants conducted in Ireland.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“… 1 Usually, it is characterized by recurrent severe vomiting separated by a long asymptomatic period. 2 It is commonly found in children even though, nowadays cases have also been reported in young adults. 1 , 2 The incidence of CVS was reported 3.15 per 1,00,000 in a study of 1,647 participants conducted in Ireland.…”
Section: Introductionmentioning
confidence: 99%
“… 2 It is commonly found in children even though, nowadays cases have also been reported in young adults. 1 , 2 The incidence of CVS was reported 3.15 per 1,00,000 in a study of 1,647 participants conducted in Ireland. 3 Studies revealed various gender distribution across the countries.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations